Impact of design variables on hydrologic and thermal performance of green, blue-green and blue roofs. Issue 2 (28th September 2022) - Almaaitah, Tamer; Drake, Jennifer; Joksimovic, Darko
Abstract: Blue-green and blue roofs are increasingly promoted to adapt to climate change by providing multiple benefits. However, uncertainties about their design and how they differ from conventional green roofs hinder their implementation. This study investigates the potential of green, blue-green, and blue roofs to control urban stormwater and improve microclimate by monitoring their performance in Toronto, Ontario, Canada. Experimental setups were built and varied with the following design factors: substrate type and thickness, drainage layer thickness and orifice size. The results revealed that blue-green roofs with organic and FLL (blended according to the German Forschungsgesellschaft Landschaftsentiwicklung Landschaftsbau) substrates significantly improved detention compared to green roofs with similar substrates. The organic blue-green roof achieved maximum retention, but FLL blue-green roof did not have higher retention than FLL green roof. The blue roof with smaller orifices had comparable hydrologic performance to vegetated roofs but suffered from long water standing durations. Organic substrates followed by FLL substrates result in the highest air cooling in the noon, but blue roofs had the highest air cooling in the evening. In-substrate temperatures in blue-green roofs were lower than those in green roofs. Trade-offs between the benefits and drawbacks need to be considered in future designs. HIGHLIGHTS: The performance of blue-green and blue roofs was assessed and compared to green roofs. Substrate type and thickness, drainage layer thickness, and orifice size influenced the hydrologic and thermal performance. Blue-green and blue roofs could provide higher control of urban runoff and improve outdoor microclimates. Trade-offs between the benefits and drawbacks need to be considered in future designs. Graphical Abstract